2018
DOI: 10.1016/j.joco.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to topical anti-glaucoma medications among patients at a tertiary hospital in North India

Abstract: PurposeThe present study aims to estimate the prevalence of non-compliance and improper drop administration technique among glaucoma patients and describe common obstacles to medication compliance.MethodsA hospital-based cross-sectional study, using standardized questionnaire and direct observation by study personnel was conducted among glaucoma patients aged 18 years and above at a tertiary care charitable eye hospital in North India. 151 consecutive glaucoma patients on medical therapy following up at the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 23 publications
1
37
1
3
Order By: Relevance
“… 20 This variation might be due to inconsistency of definition given to the level of drug adherence and a study done in Jimma used a small sample size which had only 200 glaucoma patients. This result is also higher than studies done in India (50%), 11 Iran (34%), 21 Ghana (9.9%), 22 Egypt (46.6%), 23 and Arab (50%). 24 This variation might be due to inconsistency of the definition given for the level of adherence and differences in patients group.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“… 20 This variation might be due to inconsistency of definition given to the level of drug adherence and a study done in Jimma used a small sample size which had only 200 glaucoma patients. This result is also higher than studies done in India (50%), 11 Iran (34%), 21 Ghana (9.9%), 22 Egypt (46.6%), 23 and Arab (50%). 24 This variation might be due to inconsistency of the definition given for the level of adherence and differences in patients group.…”
Section: Discussioncontrasting
confidence: 55%
“…This is in line with other studies done in different countries. 11 , 23 , 30 , 31 The disease condition is painless, progressive, and no immediate disability unless the disease reaches the end stage, due to these reason patients may not consider becoming blind and may not give attention. The other reason might be due to patient's perception of glaucoma as a curable disease after they gain a good vision secondary to mature cataract surgery was done for them.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is unique in that adherence and persistence rates in the treatment of glaucoma are relatively low compared to other chronic diseases which require lifelong therapeutic interventions [36]. Self-reported adherence rates tend to be lower than actually measured adherence rates.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the overall rate of adherence was 60% in USA, 72.1% in Canada and 72.7% in Dutch [11][12][13]. Similarly hospital based cross-sectional studies showed that in Iran 32.5%, in north India 51.6% and in Egypt 46.4% of glaucoma patients were adherent to their glaucoma medical treatment [ 5,14,15]. In Ethiopia the level of glaucoma medical treatment adherence was 32.5% at Jima University Specialized Hospital and 42.6% at Menelik II Referral Hospital [ 2,16].…”
Section: Introductionmentioning
confidence: 99%